2019
DOI: 10.1136/bmjopen-2019-029385
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of asylum-seeking caregivers on the quality of care provided by a Swiss paediatric hospital: a qualitative study

Abstract: ObjectivesThis study investigated the perspective of asylum-seeking caregivers on the quality of healthcare delivered to their children in a qualitative in-depth interview study. The health of asylum-seeking children is of key interest for healthcare providers, yet knowledge of the perspective of asylum-seeking caregivers when accessing healthcare is limited.SettingThe study took place in a paediatric tertiary care hospital in Basel, Switzerland.ParticipantsInterviews were done with 13 asylum-seeking caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 36 publications
0
26
0
5
Order By: Relevance
“…A Swedish study showed that professional interpreters are associated with the improvement of relationship between the patient and caregivers, the increase of patient safety and patient involvement in care 70. As also described in other studies, respect, friendliness and kindness led to trustful relationships and were described as important reasons for caregivers’ satisfaction with care 71. Complaints about the relationship often derived from misconceptions and misunderstandings.…”
Section: Discussionmentioning
confidence: 82%
“…A Swedish study showed that professional interpreters are associated with the improvement of relationship between the patient and caregivers, the increase of patient safety and patient involvement in care 70. As also described in other studies, respect, friendliness and kindness led to trustful relationships and were described as important reasons for caregivers’ satisfaction with care 71. Complaints about the relationship often derived from misconceptions and misunderstandings.…”
Section: Discussionmentioning
confidence: 82%
“…This allows the comparison of main diagnosis in asylum-seeking and non-asylum-seeking inpatients [ 40 ], an in-depth analysis of the subgroup of frequently visiting patients [ 41 ] as the investigation of potentially preventable hospital admissions and emergency department visits [ 42 ]. Further to this an earlier qualitative study from our institution was done to understand the perspective of the asylum-seeking families on including on aspects for the escape and the quality of care provided at the hospital [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this finding might be that asylum-seeking children are less likely to be admitted for trauma and injury as these occur less commonly. Alternatively, the injuries are equally common but asylum-seeking children potentially experience barriers to presenting to an emergency department, including lack of information about the local health care system, worries about high charges or language barriers [26][27][28].…”
Section: Discussionmentioning
confidence: 99%